The Use of Textile-Based Materials in Shell System Design in Architecture and an Evaluation in Terms of Sustainability - Tugba Alioğlu; Ayse Sirel (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The textile that has emerged from dressing and protection need of people against the variable weather conditions since the primeval ages, has gained performance characteristics with the rise of artificial fibers apart from natural fiber production and with increasing technology, and has gained a good position in architectural applications. The application areas of the textile, that was traditionally used as gear, as indoor element, and as upholstery on furniture, have been varied by emerge of smart and technical textile and its use in construction sector and architecture has been actualized. The main textile based materials used on building and skin systems are Polyvinyl Chloride (PVC), Polytetrafluoroethylene (PTFE), and Ethylene Tetra Fluoro Ethylene (ETFE). Tent, pneumatic building, canopy, pleated roof, umbrella, parasol, outer curtain, shear wall and façade are structural use forms of textile materials. While interactions between textile and architecture actualized in visual sense, structure and for, technology, and aesthetic sense, use of textile with its sustainability in architecture also brings advantages. In the paper Eden Project, Water cube, and Alliance Arena where textile based materials are used are studied. It is seen that textile material can't be handled with traditional materials, became prominent with its recycling and sustainable features.